"This is the next frontier of performance": power and knowledge in coaches "proactive" approaches to sportswomen's health. Issue 3 (2nd September 2022) - Schofield, Katherine L.; Thorpe, Holly; Sims, Stacy T.
ABSTRACT: While research has explored coach knowledge on Low Energy Availability (LEA) and Relative Energy Deficiency in Sport (RED-S), this is the first paper to explore how coaches are responding in their practices. Drawing upon semi-structured interviews with high-performance and elite coaches, this paper focuses on the experiences, lessons learnt and methods of coaches who adopt "proactive" approaches with their sportswomen regarding LEA and RED-S)related topics. Engaging a feminist poststructural approach, we explore four key themes: (i) the initial impetus to change practices, (ii) challenges encountered, (iii) strategies developed in the process of improving their own and others knowledge of LEA, and (iv) the gendered reactions and experiences of creating change. Ultimately, adopting a feminist poststructuralist lens to examine coach "proactive" approaches to sportswomen's health encourages a more critical exploration of the workings of power through knowledge and language within the highly gendered elite sport environment.